Bilateral Endometrioma Excision: Surgery-Related Damage to Ovarian Reserve. (April 2019) - Coccia, Maria Elisabetta; Rizzello, Francesca; Capezzuoli, Tommaso; Evangelisti, Paolo; Cozzi, Cinzia; Petraglia, Felice
To study whether unoperated ovarian endometrioma(s) or its surgical excision led to a modified pattern of ovarian decay with increasing female age. A sectional analysis of basal follicle stimulating hormone (FSH) and ovarian response to gonadotropins was conducted on women treated with fresh autologous In Vitro Fertilization/Intracytoplasmic sperm injection (IVF/ICSI) cycles. The study group included patients with unoperated ovarian endometrioma(s) (108 cycles); control groups were women with previous surgery for monolateral ovarian endometrioma (101 cycles), surgery for bilateral ovarian endometriomas (39 cycles), and tubal factor infertility (171 cycles). Simple linear regression analyses and the Pearson correlation were used to analyze the correlation between basal FSH, number of dominant follicles, number of retrieved oocytes, and age of patients. The relationship between the variables was significant in case of patients with nonoperated ovarian endometrioma(s) and patients with previous surgery for monolateral endometrioma and tubal factor infertility group. In patients with a history of surgery for bilateral endometriomas, no relationship was found among the variables (basal FSH 95% confidence interval [CI]: −0.475 to 0.319; P = .688; number of dominant follicles 95% CI: −0.484 to 0.382; P = .808; number of retrieved oocytes 95% CI: −0.478 to 0.370, P = .792). In women with unoperated ovarian endometrioma(s) or with a history of surgery for monolateral endometrioma, the remaining ovarian parenchyma maintains the same pattern of ovarian decay as healthy ovaries. Unoperated ovarian endometriotic lesions did not interfere with ovarian reserve and IVF/ICSI cycles' outcomes and were less injurious than surgery. After surgery for bilateral ovarian endometriomas, a decline in ovarian reserve seems independent from the patient's age.